José Veríssimo e a construção do cânone literário brasileiro: um ponto de vista estético - Pereira, Marcio Roberto [UNESP] (My University, 2014)
This essay analyses the História da literatura brasileira (1916), of José Veríssimo, that from a rupture with the romantic criticism or with the interpretation of the Scientifics method of taking as a basis a theoretical eclecticism that makes him distrust the enclosed methods and the restrict classifications. From ethnological valorization to Nationalist sentiment or from Scintificism to the support of the esthetics in the building of a Brazilian literary canon, José Veríssimo’s critical works are featured by an organicity that generates his refined criteria

Este trabalho analisa a História da literatura brasileira, de José Veríssimo, a partir de ruptura com a crítica romântica ou com a interpretação cientificista ao adotar um ecletismo teórico que o faz desconfiar dos sistemas fechados e das classificações únicas. Da valorização etnológica ao sentimento nacionalista ou do cientificismo à defesa estética da construção do cânone literário, a trajetória de José Veríssimo é marcada por uma organicidade que gera o apuramento de seus critérios.
Jose Verissimo and the Brazilian literary canon constrution: an aesthetic point of view
Keywords: Brazilian literature; José Veríssimo; Literary criticism; Canon; Literatura brasileira; José Veríssimo; Crítica literária; Cânone